Clinical Sentinel Surveillance of Equine West Nile Fever, Spain. Issue 2 (5th June 2014) - Saegerman, C.; Alba‐Casals, A.; García‐Bocanegra, I.; Dal Pozzo, F.; van Galen, G.
Summary: West Nile fever (WNF) is a viral zoonotic infection caused by a mosquito‐borne flavivirus of the Flaviviridae family. According to a comparative study, the passive surveillance of horses by equine veterinarians appeared to be the most cost‐effective system in the European context of WNF. Clinical data issued from a passive epidemiosurveillance network from September 2010 to December 2011 on horses in Spain were statistically compared and used to develop a predictive diagnostic decision tree, both with the aim to improve the early clinical detection of WNF in horses. Although clinical signs were variable in horses affected by WNF, four clinical signs and the month of occurrence were identified as useful indicators to distinguish between WNF‐related and WNF‐unrelated cases. The signs that pointed out a presumptive diagnosis of WNF in horses were cranial nerves deficits, limb paralysis, photophobia and nasal discharge. Clinical examination of horses with neurological signs that are not vaccinated against WNV could provide important clues for the early clinical detection of WNF and therefore serve as an alert for possible human viral infections. The study of the clinical pattern of WNF in horses is of importance to enhance awareness and better understanding and to optimize surveillance designs for clinical detection of WNF in horses in advance of epidemic activity affecting humans.